INFLUENCE OF BODY WEIGHT ON SEMEN CHARACTERISTICS IN SURTI BUCKS - ATARA, F B; CHAUDHARI, C F; CHAUDHARY, M M; MODI, L C; CHAUDHARI, N F; KHASATIYA, C T; BHOI, D B (The Indian Journal of Animal Reproduction, 2022)
Semen samples were collected by artificial vagina method twice in a week from nine Surti bucks.The ejaculates were divided in to three groups based on the body weight of bucks viz.,G1-up to 30 kg (n=112); G2-30.1 to 40 kg (n=98) andG3 - above 40 kg (n=78). Mean density was significantly (P<0.05) highest in G3. Semen volume (ml) was significantly (P<0.01) lower in G1. The average mass activity, progressive motility,live sperm and HOS reacted sperm were non-significantly differed between all the groups.The average sperm concentration was significantly (P<0.01) higher in G3. The mean total sperm count and semen index were significantly (P<0.01) increased with increase in body weight.The average progressive motility at 30 min intervals was non-significantly higher in G2. Average motility degeneration rate at 30, 60 and 120 min was non-significantly higher in G1. Average normal sperm percent was nonsignificantly differed between all the groups.